Characterising the impact performance of field hockey sticks - Allen, T.; Foster, L.; Carré, M.; Choppin, S. (Sports Engineering, 2012)
Published research on field hockey equipment is scarce. The aim of this research was to investigate methods for characterising the impact performance of field hockey sticks. Three sticks were used with fundamental frequencies in the range 74-154 Hz. Striking an initially still ball with a stick was identified as the preferred method for characterising performance. Impacts were simulated at mean velocities of 19 m/s at toe and 16 m/s at the shaft. The mean apparent coefficient of restitution and standard deviation were -0.32 ± 0.05 at the toe and -0.18 ± 0.02 at the shaft. The foundation work presented here provides the foundations for developing a methodology for characterising the impact performance of field hockey sticks.